1980
DOI: 10.1128/jb.143.1.499-505.1980
|View full text |Cite
|
Sign up to set email alerts
|

Unit Cell Hypothesis for Streptococcus faecalis

Abstract: The mass doubling times of exponential-phase cultures of Streptococcus faecalis were varied from 30 to 110 min by omitting glutamine from a defined growth medium and providing different concentrations of glutamate (ranging from 300 to 14 ,Ig/ml). After Formalin fixation, cells were dried by the critical point method, and carbon-platinum replicas were prepared. The surface area and volume of cell poles seen in these replicas were estimated by a computer-assisted, three-dimensional reconstruction technique. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The drift could be a random diffusion, with the machineries reaching the equator being trapped by the presence of FtsZ. The possibility of additional layering synthesis is attractive, as it would also explain the fact that the cell shape, cell volume and cell surface are constant at various growth rates, but that the amount of synthesized peptidoglycan is not (Edelstein et al, 1980). The thicker cell wall of slow-growing cells would result from the longer time available for the PBPs to relocate at the equator of ovococci.…”
Section: Open Questionsmentioning
confidence: 99%
“…The drift could be a random diffusion, with the machineries reaching the equator being trapped by the presence of FtsZ. The possibility of additional layering synthesis is attractive, as it would also explain the fact that the cell shape, cell volume and cell surface are constant at various growth rates, but that the amount of synthesized peptidoglycan is not (Edelstein et al, 1980). The thicker cell wall of slow-growing cells would result from the longer time available for the PBPs to relocate at the equator of ovococci.…”
Section: Open Questionsmentioning
confidence: 99%
“…This process occurs in discrete growth sites which are found between pairs of raised bands of wall material (8). By using electron microscopy to study replicas of exponential-phase cells which had doubled in mass between 30 and 110 min, Edelstein et al showed that both the average surface area and volume of the poles of these cells are constant and invariant with growth rate (4). These results suggest that, similar to chromosome replication, a round of envelope synthesis in S. faecium produces a constant amount of new product (i.e., two new poles) which is invariant with growth rate.…”
mentioning
confidence: 99%
“…Electron microscopy. Sample preparation was previously described for existing cell populations used in this analysis (4). Additional samples were fixed by the same method; however, they were suspended in distilled water and placed on polylysine-coated mica to minimize cell aggregation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6) indicate that this constant-size model also holds for cells during a nutritional shift. Thus, according to this scheme, once a new site is created it grows to produce two poles which do not vary in size with growth rate (6). Thus as a site approaches this maximum size (that of two finished poles) new sites must be created for the cell to continue to grow (8,15).…”
Section: Cooper Modelmentioning
confidence: 99%